Belgian experience with direct acting antivirals in people who inject drugs. (1st August 2017) - Bielen, Rob; Moreno, Christophe; Van Vlierberghe, Hans; Bourgeois, Stefan; Mulkay, Jean-Pierre; Vanwolleghem, Thomas; Verlinden, Wim; Brixko, Christian; Decaestecker, Jochen; De Galocsy, Chantal; Janssens, Filip; Cool, Mike; et al.
Highlights: A national retrospective cohort study of 579 patients (115 people who inject drugs (PWID) and 464 non-PWID). Direct acting antivirals (DAA) are effective and safe in PWID in real life. Active PWID are underserved in this real-life cohort for treatment with DAA. More efforts to reach these patients are necessary to reach the WHO targets. Abstract: Background and aim: Hepatitis C viral infection (HCV) has become a curable disease due to the development of direct acting antivirals (DAA). The WHO has set a target to eliminate HCV completely. Therefore, people who inject drugs (PWID) also need to be treated. In this study, we compared the real-life uptake and outcome of DAA treatment for HCV in PWID and non-PWID. Methods: We performed a nation-wide, retrospective cohort study in 15 hospitals. All patients who were treated with simeprevir-sofosbuvir, daclatasvir-sofosbuvir, or ombitasvir/paritaprevir ritonavir–dasabuvir between December 2013 and November 2015 were included. Results: The study population consisted of 579 patients: 115 PWID (19.9%) and 464 non-PWID (80.1%). Of the PWID 18 were active PWID (15.6%), 35 still received opiate substitution therapy (OST) (30.4%) and 62 were former PWID without OST (53.9%). PWID were more infected with genotype 1a and 3 (p = 0.001). There were equal rates of side-effects (44.7% vs. 46.6%; p = 0.847), similar rates of treatment completion (95.7% vs 98.1%; p = 0.244) and SVR (93.0% vs 94.8%; p = 0.430) between PWID and non-PWID, respectively. Conclusion: PWID, especially active users, are underserved for DAA treatment in real life in Belgium. Reimbursement criteria based on fibrosis stage make it difficult to treat PWID. Treatment adherence is similar in PWID and the general population, even in patients with active abuse. DAA were safe and effective in PWID despite the higher prevalence of difficult-to-treat genotypes. Based on these data more efforts to treat PWID are needed and policy changes are necessary to reach the WHO targets.